The Impact of Interest in Changing the Status of Unnecessary Contracts (Damascus University Journal for legal sciences, 2025)
The nature of contracts in Islamic law is based on achieving interests between the contractors, and not harming them, the character of some unnecessary contracts may change to become necessary in observance of the interest, and in this research a study of the effect of interest on changing the status of unnecessary contracts in some financial contracts, such as Istisna, naked, and farming, as the research deals with the statement of the contract’s truth, the necessity of necessity, as it deals with a statement of truth The interest and the statement of its divisions, then divided the research into three topics, the first and showed the effect of the interest in changing the status of the Istisna'a contract, which is an unnecessary contract for the ancient jurists except that the contemporary jurists went to say that it is necessary by simply formulating the requirements of the interest and raising the harm, and the second and showed the effect of the interest in changing the adjective of the nude contract that is originally a contract that is not necessary except that it is not necessary It is obligatory if the return of the standard results in harm to the borrower, and in the third it showed the effect of the interest in changing the character of the farmer contract, and this research concluded that the interest has an effect in changing the character of some unnecessary contracts such as Istisna, naked and farming.
Keywords: Contracts; Change; Necessity; interest